Línguas de ritmo silábico - Cagliari, Luiz Carlos [UNESP] (My University, 2012)
One of the most controversial issues in the history of Phonetics is the discussion about the typology of speech rhythm. Out of the Greek and Latin tradition on poetry versification, the notion of rhythm has been misunderstood as speech rate. In the early years of the 20th century, a dichotomy merged classifying the speech rhythm into stress-timed and syllable-timed languages, inspired by the old theory of poetic versification. Following the same old pattern, later on, a third type of language were proposed: the moraic languages, initially attributed only to Japanese. With the facilities to carry on acoustic research, in the second half of the 20th century, the typology of language rhythm came to a dead end. Different types of language were set out. This paper discusses these ideas, showing a great misunderstanding among researchers in relation to the characterization of a syllable-timed language. The notion of mora is revisited and its role in the study of speech rhythm is better defined.

Uma das questões mais polêmicas da história da Fonética é, sem dúvida, a discussão sobre a tipologia rítmica das línguas. Fora da tradição greco-latina da versificação poética, a noção de ritmo foi confundida com a velocidade de fala, por muito tempo. No começo do século passado, surgiu a ideia da dicotomia entre língua de ritmo acentual e língua de ritmo silábico, também fortemente influenciada pela teoria da versificação poética. Nesse mesmo contexto, surgiu um terceiro tipo de língua, chamado de língua de ritmo moraico e aplicado quase exclusivamente ao japonês. Com as pesquisas acústicas e tratamentos estatísticos de dados gerados por análises eletrônicas computacionais da fala, a tipologia rítmica das línguas ficou mais confusa, com o surgimento de vários tipos de língua quanto ao ritmo. O presente trabalho discute algumas dessas ideias, mostrando que houve um grande equívoco por parte de alguns pesquisadores quanto à caracterização das línguas de ritmo silábico. A noção de moras é revisitada e seu papel é melhor definido nos estudos rítmicos da fala.
Syllable-timed languages
Keywords: Rhythm; Mora; History of speech rhythm; Ritmo silábico; Prosódia; Tipologia do ritmo